Expression of a lymphatic endothelial cell marker in benign and malignant vascular tumors. - Xu, H; Edwards, JR; Espinosa, O; Banerji, S; Jackson, D; Athanasou, N (2004)
Tumors of endothelial cell origin are relatively common. Soft tissue tumors and numerous subtypes of benign and malignant vascular tumors have been described; the histogenesis of many of these tumors is uncertain, and distinguishing between benign and malignant vascular tumors, some of which express lymphatic endothelial cell markers, can be problematic. In the present study, immunophenotypic expression of a novel hyaluronan receptor (LYVE-1), which is expressed by endothelial cells of normal lymphatic vessels but not blood vessels, was determined in benign and malignant vascular tumors. It was found that, except in lymphangiomas, intramuscular hemangiomas, and Masson's hemangiomas, endothelial cells in benign blood vessel tumors (including capillary and cavernous hemangiomas, glomus tumors, pyogenic granulomas, and epithelioid hemangiomas) were negative for LYVE-1, and that all angiosarcomas and Kaposi's sarcomas were positive for LYVE-1. Expression of LYVE-1 and other lymphatic endothelial cell markers in relatively few vascular neoplasms has implications for the histogenesis of these lesions, and may prove useful in distinguishing angiosarcoma and Kaposi's sarcoma from most common benign vascular tumors.